Is it just motion that silences awareness of other visual changes? - Pierce, Jonathan (2013)
When an array of visual elements is changing color, size, or shape incoherently, the changes are typically quite visible even when the overall color, size, or shape statistics of the field may not have changed. When the dots also move, however, the changes become much less apparent; awareness of them is “silenced” (Suchow & Alvarez, 2011). This finding might indicate that the perception of motion is of particular importance to the visual system, such that it is given priority in processing over other forms of visual change. Here we test whether that is the case by examining the converse: whether awareness of motion signals can be silenced by potent coherent changes in color or size. We find that they can, and with very similar effects, indicating that motion is not critical for silencing. Suchow and Alvarez's dots always moved in the same direction with the same speed, causing them to be grouped as a single entity. We also tested whether this coherence was a necessary component of the silencing effect. It is not; when the dot speeds are randomly selected, such that no coherent motion is present, the silencing effect remains. It is clear that neither motion nor grouping is directly responsible for the silencing effect. Silencing can be generated from any potent visual change.